ANALYSIS OF COMPANY VALUE ANTECEDENTS IN LQ45 INDEX COMPANIES 2018-2023 - Reni Anggraeni; Agung Budi (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze the influence of investment decisions, funding decisions and dividend policies on the value of LQ45 index companies listed on the Indonesia Stock Exchange. The period used in this research is 5 (five) years, starting from 2018-2023. This research uses quantitative research. The population in this study was 45 companies listed on the LQ45 index during the research period. The sampling technique used was purposive sampling and a sample of 8 companies was obtained. The data analysis technique used is panel data regression. The research results show that investment decision variables have a partial and significant effect on company value. while company value has no influence on funding decisions and dividend policy.